Penggunaan Platform Pembelajaran Online oleh Guru PAI - Gina Yuliani; Muhiddinur Kamal; Iswantir Iswantir; Zulfani Sesmiarni (Tarbiyah Wa Ta'lim: Jurnal Penelitian Pendidikan dan Pembelajaran, 2022)
The purpose of this study was to find out how the use of online learning platforms by PAI teachers at SMPN 9 Mandau, Mandau District, Bengkalis Regency, Riau Province. This research is descriptive with a qualitative paradigm using accidental sampling technique. Key informants are PAI teachers, while supporting informants are principals and students. The techniques of data collection in this study are interview, observation, and documentation techniques. The data analysis technique consists of data reduction, data presentation and drawing conclusions or data verification. Testing the validity of the data is done through data triangulation. The results showed that the learning media used in helping the teaching and learning process were Zoom Meeting, WhatsApp, and Google Classroom media. Constraints in the use of learning media include difficulties in buying packages, network disturbances, not understanding the material, and limitations of learning media. The solution in using these learning media is to do face-to-face and online learning (hybrid learning), using media that students understand, internet quota assistance, training in the manufacture of learning media.